IMPLEMENTATION OF PROJECT BASED LEARNING ( PJBL ) FOR INCREASE REASONING STUDENT CRITICAL THINKING AND CREATIVITY THROUGH POP UP BOOK WORKS - Upit Witasari; Lilik Sri Hariani; Endang Surjati; Yuli Ifana Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Science learning demands development reasoning critical and creative student as part from learning meaningful , but practice learning conventional in schools base Not yet fully capable facilitate ability the optimally . Conditions This show the need application of learning models innovative and capable push involvement active student in the learning process . Research This use approach quantitative with quasi - experimental design involving student Class IV of SDN Arjosari 1 Malang City which is divided into become class experiments and classes control . Class experiment given treatment in the form of learning using the Project Based Learning ( PjBL ) model assisted by Pop Up Book media, while class control use learning conventional . Data collection was carried out through test reasoning critical and creativity at the pretest and posttest stages that have been arranged based on indicator think level high , then analyzed use technique statistics inferential For know differences and improvements results Study between group . Research results show existence difference as well as improvement significant reasoning critical and creative students in classes that implement Project Based Learning assisted by Pop Up Book media compared to with learning conventional . Students in class experiment show more capabilities​ Good in put forward ideas, analyze information , complete problems , and produce creative and meaningful work​ through project learning . In addition , involvement active student in every stages PjBL participate contribute to increasing motivation and independence learning . The application of Pop Up Book media also helps student understand draft diversity culture in a way more concrete and interesting , so learning become more contextual . With Thus , the PjBL model assisted by Pop Up Book is able increase quality active , contextual and meaningful science and science learning at school base as well as worthy implemented as alternative learning innovative support​ development reasoning critical and creative student .